Limonene in exhaled breath is elevated in hepatic encephalopathy. (21st November 2016) - O'Hara, M E; Fernández del Río, R; Holt, A; Pemberton, P; Shah, T; Whitehouse, T; Mayhew, C A
Abstract: Breath samples were taken from 31 patients with liver disease and 30 controls in a clinical setting and proton transfer reaction quadrupole mass spectrometry (PTR-Quad-MS) used to measure the concentration of volatile organic compounds (VOCs). All patients had cirrhosis of various etiologies, with some also suffering from hepatocellular cancer (HCC) and/or hepatic encephalopathy (HE). Breath limonene was higher in patients with No-HCC than with HCC, median (lower/upper quartile) 14.2 (7.2/60.1) versus 3.6 (2.0/13.7) and 1.5 (1.1/2.3) nmol mol −1 in controls. This may reflect disease severity, as those with No-HCC had significantly higher UKELD (United Kingdom model for End stage Liver Disease) scores. Patients with HE were categorized as having HE symptoms presently, having a history but no current symptoms and having neither history nor current symptoms. Breath limonene in these groups was median (lower/upper quartile) 46.0 (14.0/103), 4.2 (2.6/6.4) and 7.2 (2.0/19.1) nmol mol −1, respectively. The higher concentration of limonene in those with current symptoms of HE than with a history but no current symptoms cannot be explained by disease severity as their UKELD scores were not significantly different. Longitudinal data from two patients admitted to hospital with HE show a large intra-subject variation in breath limonene, median (range) 18 (10–44) and 42 (32–58) nmol mol −1 .